Analisis Pola Interaksi Sosial Remaja Siswa SMP Negeri 57 Jakarta - Izah Aulia; Abdul Haris Fatgehipon; Nova Scorviana H. (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Social life is supported by factors such as continuous and mutually influential social interactions. Social interaction has an important role in the social development of adolescents. The aim of this research is to determine the patterns of social interaction carried out by teenage students at SMP Negeri 57 Jakarta. This research uses qualitative research methods with data collection techniques through interviews and descriptive data analysis. The results obtained in this research are that the patterns of social interaction carried out by students are formed from factors in the form of imitation, suggestion, identification and sympathy. Apart from being supported by social interaction factors, the interaction patterns carried out by students are also based on the conditions for social interaction, namely communication and social contact.